(untitled) (Eurasian Research Bulletin, 2025)
This article examines the role and importance of political parties in the socio-political and spiritual life of society. Political parties are institutions that play an important role in forming political views in society, participating in state administration, and protecting the interests of the people. The article analyzes the mediating functions of political parties between the state and citizens, their influence on social and economic processes in society, as well as the role of parties in the development of political culture